Young Undocumented Migrants in Contemporary Fiction Films: Guten Tag, Ramón and Ya no estoy aquí - Ricardo Quintana Vallejo (Norteamérica)
The last fifteen years have seen a rise in critically-acclaimed fiction films depicting undocumented migration from and through Mexico. By analyzing two illustrative examples—Guten Tag, Ramón (2013), and Ya no estoy aquí (2019)—this paper uses the framework of the coming-of-age genre to dissect the characteristics of this new contemporary cinematographic type, thus pondering its inner-workings and appeal. Moreover, the paper contrasts different factions of the critical reception these films in order to examine why such films are met with both punitive disdain and enthusiastic celebration. The differences in tone between these two films show how the themes of migration, poverty, and violence can be interpreted in varied ways that serve to call attention to their urgency. From the lighthearted humor of Guten Tag, Ramón to the poignant solemnity of Ya no estoy aquí, the cinematographic genre, so close to the archetypal plot of coming-of-age narratives, denounces both the indifference of the Mexican middle class and the xenophobic settings that seek to undermine the right to migrate.